Simultaneous assessment of oxygen- and nitrate-based net community production in a temperate shelf sea from a single ocean glider - T. Hull (Copernicus Publications, 2021)
The continental shelf seas are important at a global scale for ecosystem services. These highly dynamic regions are under a wide range of stresses, and as such future management requires appropriate monitoring measures. A key metric to understanding and predicting future change are the rates of biological production. We present here the use of an autonomous underwater glider with an oxygen (O2) and a wet-chemical microfluidic total oxidised nitrogen (NOx-=NO3-+NO2-<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="109pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="409333b671deea5f9edff7765dfec49e"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-18-6167-2021-ie00001.svg" width="109pt" height="15pt" src="bg-18-6167-2021-ie00001.png"/></svg:svg>) sensor during a spring bloom as part of a 2019 pilot autonomous shelf sea monitoring study. We find exceptionally high rates of net community production using both O2 and NOx-<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="31pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="d9c234e39184fff862105df14f04120f"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-18-6167-2021-ie00002.svg" width="31pt" height="14pt" src="bg-18-6167-2021-ie00002.png"/></svg:svg> water column inventory changes, corrected for air–sea gas exchange in case of O2. We compare these rates with 2007 and 2008 mooring observations finding similar rates of NOx-<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="31pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="a4c4c99bafc2a48051e735ec178221a8"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-18-6167-2021-ie00003.svg" width="31pt" height="14pt" src="bg-18-6167-2021-ie00003.png"/></svg:svg> consumption. With these complementary methods we determine the O2:N amount ratio of the newly produced organic matter (7.8 ± 0.4) and the overall O2:N ratio for the total water column (5.7 ± 0.4). The former is close to the canonical Redfield O2:N ratio of 8.6 ± 1.0, whereas the latter may be explained by a combination of new organic matter production and preferential remineralisation of more reduced organic matter at a higher O2:N ratio below the euphotic zone.